2014
DOI: 10.3329/bjmed.v24i2.20219
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidities among epilepsy patients: experience in Bangladesh

Abstract: Abstract:Objective: To determine comprehensively all the major comorbid diseases observed among epilepsy patients. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Huttenlocher & Hapke 23 found that the majority of children with uncontrollable seizures (61%) were mentally retarded and remission of seizures was much less frequent (1.5%/ year) in this group with mental retardation. One Bangladeshi study Chowdhury RN et al 15 showed that Mental retardation was more common and significantly associated (p=0.0001) with generalized epilepsy patients.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation
“…Huttenlocher & Hapke 23 found that the majority of children with uncontrollable seizures (61%) were mentally retarded and remission of seizures was much less frequent (1.5%/ year) in this group with mental retardation. One Bangladeshi study Chowdhury RN et al 15 showed that Mental retardation was more common and significantly associated (p=0.0001) with generalized epilepsy patients.…”
Section: Acknowledgementmentioning
confidence: 99%
“…This factor contributes to higher rates of uncontrollable seizures and neuropsychiatric complications. One Bangladeshi study showed that the neuropsychiatric, developmental and pain disorders are quite common co morbid conditions among epilepsy patients 15 .…”
Section: Introductionmentioning
confidence: 99%